Compressive Strength of Timber by Ultrasonic Pulse Technique - Sanyal, S. N.; Gulati, A. S. (Indian Forester, 1979)
Ultrasonic pulse techniques in the field of non-destructive testing of muterials are well known. In the present work an attempt has been made to determine the relationship between compressive strength and ultrasomic velocity along the grain in timber. Ultrasonic velocity in several Indian timber species were measured with the help of Ultrasonic tester and the specimens were then subjected to determine the compressive strength parallel to the grain with conventional test methods. From the data so obtained, a relationship has been established, which can be very well utilised in determining compressive strength of different timber members or the stractures io ’Situ’